Improving Diabetic Retinopathy Screening Among Patients With Diabetes Mellitus Using the Define, Measure, Analyze, Improve, and Control Process Improvement Methodology. Issue 2 (March 2021) - Kollipara, Usha; Varghese, Shilu; Mutz, Jackie; Putra, Joseph; Bajaj, Puneet; Mirfakhraee, Sasan; Tessnow, Alex; Fish, Jason; Ali, Sadia
ABSTRACT: Diabetic retinopathy, a complication of diabetes mellitus (DM), is the leading cause of blindness in the United States. Early detection and appropriate timely treatment would result in 50–70% reduction in blindness due to DM, with a positive economic impact on patients and the healthcare system. The purpose of our project is to improve screening rates for retinopathy among patients with DM seen in a large endocrinology clinic applying the Lean Six Sigma Define, Measure, Analyze, Improve, and Control project framework and clinical decision support tools embedded in the electronic health record (EHR). Retinopathy screening rates improved from 49% to 72% by the end of the project. Interventions included identifying care gaps using a population registry, patient outreach through the electronic medical record patient portal, placing referrals to ophthalmology, improving documentation in health maintenance, and tracking improvement for sustainability. Our results demonstrate that process improvement methodologies and EHR tools can be successfully applied to improve care and clinical outcomes in patients with DM.